ANALISIS KEPUASAN PENGGUNA FASILITAS PARK AND RIDE LEBAK BULUS DENGAN METODE FUZZY SERVICE QUALITY - Ghinda Lianny Santang; Eri Setia Romadhon (FTSP Universitas Jayabaya, 2022)
The park and ride facility at Lebak Bulus Grab Station is a facility provided to increase public interest in switching from private vehicles to public transportation, in this case the Jakarta MRT, so the purpose of this research is to determine the level of park and ride customer satisfaction and find out what items need conducted to improve service quality. Subjects in this study consisted of 200 respondents. The data collection technique was carried out by filling out a questionnaire/questionnaire. This questionnaire is used to assess the Likert scale from 1 strongly disagree, 2 disagree, 3 neutral. 4 agreed, 5 strongly agreed. The validity test process resulted in all statement items being declared valid because they exceeded the r table, namely 0.138 and the reliability test was declared passed because it exceeded 0.6 in Cronbach alpha. Fuzzy sets are determined with a value of 0 to 1 where for